Tantalum-tungsten alloy and short-process preparation method thereof

By using the TA-10W spherical powder and spherical pink mixed and laser constituency melting process to prepare tungsten alloy, and high vacuum exfoliating heat treatment, solve the complex, long cycle, and difficult to be difficult to prepare in existing technologies. The problem of control has achieved the effect of simplifying the process, shortening of preparation cycles, improving mechanical performance, and cost reduction.

CN119328162APending Publication Date: 2025-01-21NINGXIA ORIENT INTELLIGENT MANUFACTURING TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411504821.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-27
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing tantalum tungsten alloy preparation process is complex, the cycle is long, the tungsten content is difficult to accurately control, and the mechanical properties of the finished product are unstable.

Method used

Ta-10W spherical powder is used as the base material, and the tantalum-tungsten alloy is prepared by mixing it with spherical tantalum powder in different proportions and using a laser selective melting process, followed by high vacuum stress relief heat treatment.

Benefits of technology

Simplified process flows, shorten the preparation cycle, achieved precise control of tungsten content, improved the uniformity and mechanical performance of the alloy composition, and reduced production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119328162A_ABST
    Figure CN119328162A_ABST
Patent Text Reader

Abstract

The medium-temperature radial forging method comprises the steps that pretreatment is conducted, specifically, a niobium-tungsten alloy extrusion bar blank is heated for 60-180 minutes at the temperature of 750-950 DEG C, rapid forging and straightening are conducted, and a medium-temperature radial forging bar blank is obtained and annealed for 60-120 minutes at the temperature of 1250-1450 DEG C; medium-temperature radial forging is conducted, specifically, a two-step method is adopted, in the first step, a bar blank is preheated to 80-100 DEG C and coated with Ta1350 high-temperature glass powder, heat preservation is conducted for 90-180 minutes at the temperature of 1050-1150 DEG C, and the bar blank is forged into a bar with the diameter of 70 + / -1 mm in the mode that the diameter is reduced by 7-10 mm every time; and in the second step, the heating and coating processes are repeated, the diameter is reduced by 5-7 mm every time, and the bar with the required specification is manufactured. By optimizing the medium-temperature forging and annealing process, the fine grain structure is controlled, the high-temperature mechanical property, creep resistance and oxidation resistance of the material are improved, and the material is suitable for aerospace engines and other high-temperature and high-pressure scenes. Compared with a traditional method, the technology improves the yield, shortens the production period, reduces the labor intensity, is suitable for large-scale production, reduces surface air suction, oxidation and burning loss, and improves the production efficiency and the finished product quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of tantalum-tungsten alloy preparation, and in particular to a tantalum-tungsten alloy and a short-process preparation method thereof. Background Art

[0002] Tantalum tungsten alloy has far-reaching application prospects in the aerospace and military fields due to its excellent high temperature performance and corrosion resistance. However, tantalum tungsten alloy has high hardness and melting point, which makes it difficult to process with traditional methods, with low material utilization, long processing cycle, and difficult to prepare complex parts. As tantalum tungsten alloy is widely used, the preparation of tantalum tungsten alloy with different tungsten contents also faces the above problems.

[0003] As the structure of tantalum-tungsten alloy products becomes more complex, the preparation of products with different tungsten contents requires the process of ingot melting → forging → heat treatment → machining → welding. The raw material preparation cycle is long and the yield rate is low.

[0004] The following three patents were found through the query: CN202110592195.3 "Tantalum-tungsten alloy preparation process and tantalum-tungsten alloy based on laser selective melting" and CN202011584417.9 "A tantalum-tungsten alloy for 3D printing and preparation of tantalum-tungsten alloy thin-walled plates", and ZL202210885960.5 "Tantalum-tungsten alloy products and preparation methods thereof", which involve the preparation of tantalum-tungsten alloy products.

[0005] In patent CN202110592195.3 "Tantalum-tungsten alloy preparation process and tantalum-tungsten alloy based on laser selective melting", Ta88W12 is used as the printing material and laser selective melting technology is used to prepare the properties shown in Table 1.

[0006] Table 1Ta88W12 printing performance

[0007] sample W content (%) Rm(MPa) Rp0.2(MPa) A(%) Remark Ta88W12 12 880 830 8

[0008] From the above data, the tensile strength and yield strength are high, but its elongation is only 8%.

[0009] Patent CN202011584417.9 "A tantalum-tungsten alloy for 3D printing and preparation of tantalum-tungsten alloy thin-walled plates" uses a single-base spherical tantalum powder and a spherical tungsten powder as the mixture. The performance after printing is relatively low. Due to the differences in density, fluidity, and melting point of the two single-base powders, they cannot be mixed evenly during the mixing process. As a result, after laser selective melting and forming, there is component segregation in the internal structure. The different melting points lead to pore defects, and the ideal density cannot be achieved, which will directly affect the mechanical properties of the printed components.

[0010] In Patent ZL202210885960.5 "Tantalum-tungsten alloy products and preparation methods thereof", the printed products and raw materials are the same raw materials. The tantalum-tungsten product method requires printing after melting the raw material ingots and preparing spherical powder, and the cycle is relatively long.

[0011] However, the previous tantalum-tungsten alloy preparation method requires smelting the raw material ingot, melting the tantalum powder and tungsten powder, and going through multiple processes to prepare raw materials that meet different tungsten contents. The processing cycle is long, and the tungsten content regulation is complex and difficult to control. The prepared raw materials also require subtractive processing or welding processing to prepare products that meet the requirements, such as turning and milling. The processing is difficult, the yield rate is low, and the cost is high, which cannot meet the needs of today's market. Due to the above problems, a short-process tantalum-tungsten alloy preparation method has been specifically introduced. Summary of the invention

[0012] The purpose of the present invention is to provide a short-process tantalum-tungsten alloy preparation method to solve the problems of complex tantalum-tungsten alloy preparation process, long cycle, difficulty in accurately controlling tungsten content, and unstable mechanical properties of finished products in the prior art.

[0013] To achieve the above object, the present invention provides the following technical solutions:

[0014] A short-process tantalum-tungsten alloy preparation method comprises the following steps:

[0015] (1) providing Ta-10W spherical powder as a substrate, wherein the Ta-10W spherical powder has a tantalum content of 90% and a tungsten content of 10%, calculated by mass fraction;

[0016] (2) mixing the Ta-10W spherical powder and the spherical tantalum powder in different proportions, wherein the tungsten content in the mixed powder is 0-10% by mass fraction;

[0017] (3) treating the mixed powder by a laser selective melting process, and melting and forming a tantalum-tungsten alloy having a tungsten content of 0-10% by mass by adjusting parameters such as laser power, scanning speed, scanning spacing and layer thickness;

[0018] (4) The formed tantalum-tungsten alloy is subjected to high vacuum stress relief heat treatment to ensure the density and stability of the alloy.

[0019] Preferably, the mixing ratio of the Ta-10W spherical powder and the spherical tantalum powder is such that the tungsten content in the mixed powder is greater than 0% and less than 10%, calculated by mass fraction.

[0020] Preferably, the mixing ratio of the Ta-10W spherical powder and the spherical tantalum powder is such that the tungsten content in the mixed powder is 2.5% to 7.5% by mass.

[0021] Preferably, the particle size of the Ta-10W spherical powder is 15-53 μm, and the sphericity is greater than 99%, and the particle size of the spherical tantalum powder is 15-53 μm, and the sphericity is greater than 99%.

[0022] Preferably, the parameters of the laser selective melting process are: laser power of 375 to 450 W, scanning speed of 550 to 750 mm / min, scanning spacing of 0.1 mm, and layer thickness of 0.03 mm.

[0023] Preferably, the vacuum degree of the stress relief heat treatment is less than 3×10 -3 Pa, temperature is 1250℃ to 1400℃.

[0024] Preferably, the chemical composition of the spherical tantalum powder satisfies the following conditions:

[0025] Carbon content ≤7ppm,

[0026] Hydrogen content ≤17ppm,

[0027] Oxygen content ≤160ppm,

[0028] Nitrogen content ≤20ppm,

[0029] The purity of tantalum is greater than 99.995%.

[0030] Preferably, the chemical composition of the Ta-10W spherical powder satisfies the following conditions:

[0031] Carbon content ≤7ppm,

[0032] Hydrogen content ≤15ppm,

[0033] Oxygen content ≤100ppm,

[0034] Nitrogen content ≤20ppm,

[0035] Iron content ≤3ppm,

[0036] The tungsten content is 9-11%,

[0037] The contents of other impurities such as nickel, silicon, niobium and titanium meet the standard requirements.

[0038] The tantalum-tungsten alloy prepared according to the above method has a tensile strength Rm of 550 to 726 MPa, a yield strength Rp0.2 of 473 to 665 MPa, and an elongation A of 29% to 40%.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] Simplified process flow and shortened preparation cycle: The present invention adopts Ta-10W spherical powder as the base material and combines it with laser selective melting technology to achieve short-process preparation of tantalum-tungsten alloy, eliminating complex processes such as ingot casting, forging, heat treatment and mechanical processing in traditional methods, thereby greatly shortening the alloy preparation cycle.

[0041] Tungsten content is precisely and stably controlled: Compared with the traditional preparation method of mixing tantalum powder and tungsten powder, the present invention uses Ta-10W spherical powder as the base material and achieves precise control of tungsten content by evenly mixing tantalum powder in different proportions, thus avoiding component segregation caused by density differences and ensuring the composition uniformity and performance stability of tantalum-tungsten alloy.

[0042] High efficiency and low cost: The present invention uses laser selective melting technology, which can not only efficiently produce tantalum-tungsten alloy products with different tungsten contents, but also avoid the high material consumption and complicated processing in traditional manufacturing methods, thereby significantly reducing production costs.

[0043] Excellent mechanical properties: Through precise control of laser selective melting process parameters, the tantalum-tungsten alloy prepared by the present invention has excellent mechanical properties, especially showing significant improvement in tensile strength and yield strength, which can meet the needs of various high-strength applications.

[0044] High material utilization rate, suitable for complex structural parts: Laser selective melting technology can directly form tantalum-tungsten alloy products with complex shapes, reducing material waste, improving material utilization rate, and providing technical support for the manufacture of highly complex structural parts. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is the metallographic test result of the sample obtained in Example 1 under a 50x field of view.

[0046] Figure 2 This is the metallographic test result of the sample obtained in Example 1 at a 200-fold field of view.

[0047] Figure 3 This is the metallographic test result of the sample obtained in Example 2 under a 50x field of view.

[0048] Figure 4 This is the metallographic test result of the sample obtained in Example 2 at a 200-fold field of view.

[0049] Figure 5 This is the metallographic test result of the sample obtained in Example 3 under a 50x field of view.

[0050] Figure 6 This is the metallographic test result of the sample obtained in Example 3 at a 200-fold field of view. DETAILED DESCRIPTION

[0051] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0052] The embodiments of the present invention are implemented according to the following steps:

[0053] (1) providing Ta-10W spherical powder as a substrate, wherein the Ta-10W spherical powder has a tantalum content of 90% and a tungsten content of 10%, calculated by mass fraction; the particle size of the Ta-10W spherical powder is 15-53 μm, and the sphericity is greater than 99%;

[0054] (2) mixing Ta-10W spherical powder and spherical tantalum powder in different proportions, wherein the particle size of the spherical tantalum powder is 15-53 μm, the sphericity is greater than 99%, and the mixing ratio of the Ta-10W spherical powder and the spherical tantalum powder is such that the tungsten content in the mixed powder is 2.5% to 7.5%, calculated by mass fraction;

[0055] (3) The mixed powder is processed by a laser selective melting process, the parameters of the laser selective melting process are: laser power of 375 to 450 W, scanning speed of 550 to 750 mm / min, scanning spacing of 0.1 mm, layer thickness of 0.03 mm, so that the tungsten content is 0-10%, and the tantalum-tungsten alloy is melted and formed by mass fraction;

[0056] (4) The formed tantalum-tungsten alloy is subjected to high vacuum stress relief heat treatment to ensure the compactness and stability of the alloy. The vacuum degree of stress relief heat treatment is less than 3×10 -3 Pa, temperature is 1250℃ to 1400℃.

[0057] The chemical composition of spherical tantalum powder meets the following conditions:

[0058] Carbon content ≤7ppm,

[0059] Hydrogen content ≤17ppm,

[0060] Oxygen content ≤160ppm,

[0061] Nitrogen content ≤20ppm,

[0062] The content of other impurities meets the requirements of YY / T 0966-2014RO5200 (Pure Tantalum for Surgical Implant Metal Materials).

[0063] The purity of tantalum is greater than 99.995%.

[0064] The chemical composition of Ta-10W spherical powder meets the following conditions:

[0065] Carbon content ≤7ppm,

[0066] Hydrogen content ≤15ppm,

[0067] Oxygen content ≤100ppm,

[0068] Nitrogen content ≤20ppm,

[0069] Iron content ≤3ppm,

[0070] The tungsten content is 9-11%,

[0071] The contents of other impurities such as nickel, silicon, niobium and titanium meet the requirements of GJB 9572-2018 standard.

[0072] The tantalum-tungsten alloy prepared according to the above method has a tensile strength Rm of 550 to 726 MPa, a yield strength Rp0.2 of 473 to 665 MPa, and an elongation A of 29% to 40%.

[0073] Example

[0074] Table 2 Example Powder Control Comparison Table

[0075]

[0076]

[0077] Take the tantalum 10 tungsten powder and tantalum spherical powder in Table 2, mix them into a mixer, with an effective working volume of 10 liters, a spindle speed of 25 r / min, a maximum inclination angle of 105 degrees, and a mixing cycle of 5-20 min. After mixing evenly, weigh the spherical powder again.

[0078] Using a single laser selective melting device, the parameters of each group of mixed tantalum-tungsten powders are debugged. The debugging scheme is shown in Table 3.

[0079] Table 3 Parameter control of laser selective melting

[0080] Serial number Powder Power(W) Speed(mm / min) Spacing(mm) Layer thickness (mm) Example 1 Tantalum 2.5 Tungsten 375-410 650-750 0.1 0.03 Example 2 Tantalum 5 Tungsten 380-425 600-700 0.1 0.03 Example 3 Tantalum 7.5 Tungsten 400-450 550-680 0.1 0.03

[0081] The stress relief vacuum heat treatment is completed in a high vacuum heat treatment furnace to ensure that the tantalum-tungsten alloy parts are not oxidized during the heat treatment.

[0082] Test results:

[0083] Figure 1-6The results of metallographic structure detection of tantalum-tungsten alloys with different tungsten contents are shown. The metallographic structure performance of different powders under 50x and 200x viewing fields is mainly analyzed. It can be seen that the three groups of samples have fewer pore defects, with a small amount of pores in Examples 1 and 2, and almost no pore defects in Example 3. By properly regulating the process parameters, the uniformity of the metallographic structure can be improved, defects can be reduced, and the overall performance of the tantalum-tungsten alloy can be improved.

[0084] The samples of Examples 1 and 2 were printed with pure tantalum and Ta10W and then subjected to mechanical property testing. The performance reached the ideal value. The test results are shown in Table 4.

[0085] Table 4 Room temperature detection performance comparison table

[0086] Sample No. W content (%) Rm(MPa) Rp0.2(MPa) A(%) Remark Pure Tantalum No. 1 Sample 0 314.4 263.1 35.2 Pure Tantalum No. 2 Sample 0 325.9 274.6 40.8 Sample No. 1 of Example 1 2.5 467.6 388.9 33.6 Sample No. 2 of Example 1 2.5 467.7 392.2 34.8 Sample No. 1 of Example 2 5 550.9 473.4 30.4 Sample No. 2 of Example 2 5 547.9 475.4 29.2 Ta10W Sample No. 1 10 717.0 656.5 29.6 Substrate Ta10W Sample No. 2 10 726.4 665.2 29.2 Substrate

[0087] From the test results in Table 4, we can see the following trends and characteristics:

[0088] Tantalum powder samples with 0% tungsten content (Ta-1 and Ta-2) exhibit lower tensile strength and yield strength, but higher elongation, which are 35.2% and 40.8%, respectively, which indicates that pure tantalum material has better plasticity.

[0089] Alloy samples with 2.5% tungsten content (Ta2.5W-1 and Ta2.5W-2) showed significantly improved tensile strength and yield strength, with tensile strength from 467.6MPa to 467.7MPa, and yield strength from 388.9MPa to 392.2MPa, while elongation decreased slightly, remaining between 33.6% and 34.8%. Compared with pure tantalum, the strength of the material increased significantly after adding 2.5% tungsten, while the plasticity decreased slightly.

[0090] The alloy samples with 5% tungsten content (Ta5W-1 and Ta5W-2) showed further enhanced strength, with tensile strength reaching 550.9MPa and 547.9MPa, yield strength of 473.4MPa and 475.4MPa, and elongation continued to decrease to 29.2%-30.4%. This shows that with the increase of tungsten content, the strength of the material is significantly improved, but the plasticity is weakened.

[0091] The alloy samples with 10% tungsten content (Ta10W-1 and Ta10W-2) showed the highest strength, with tensile strength of 717.0MPa and 726.4MPa, yield strength of 656.5MPa and 665.2MPa, and elongation of 29.2%-29.6%. Compared with the samples with low tungsten content, the strength of the alloy reached the highest value after the tungsten content increased to 10%, but the elongation remained at a low level, indicating that while obtaining high strength, the ductility of the material was weakened.

[0092] Summary: The results in Table 4 show the regular changes in the mechanical properties of tantalum-tungsten alloys with different tungsten contents. With the increase of tungsten content, the tensile strength and yield strength of the alloy continue to increase, but the elongation shows a downward trend. This shows that the addition of tungsten can significantly improve the strength of the alloy, but has a certain negative impact on the plasticity of the material. Therefore, in practical applications, it is necessary to select an appropriate tungsten content according to specific needs to balance the strength and ductility of the material.

[0093] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A short-process preparation method of tantalum-tungsten alloy, characterized in that: The following steps are involved: (1) providing Ta-10W spherical powder as a substrate, wherein the Ta-10W spherical powder has a tantalum content of 90% and a tungsten content of 10%, calculated by mass fraction; (2) mixing the Ta-10W spherical powder and the spherical tantalum powder in different proportions, wherein the tungsten content in the mixed powder is 0-10% by mass fraction; (3) treating the mixed powder by a laser selective melting process, and melting and forming a tantalum-tungsten alloy having a tungsten content of 0-10% by mass by adjusting parameters such as laser power, scanning speed, scanning spacing and layer thickness; (4) The formed tantalum-tungsten alloy is subjected to high vacuum stress relief heat treatment to ensure the density and stability of the alloy.

2. The preparation method according to claim 1, characterized in that: The mixing ratio of the Ta-10W spherical powder and the spherical tantalum powder is such that the content of tungsten in the mixed powder is greater than 0% and less than 10%, calculated by mass fraction.

3. The preparation method according to claim 2, characterized in that: The mixing ratio of the Ta-10W spherical powder and the spherical tantalum powder is such that the content of tungsten in the mixed powder is 2.5% to 7.5% by mass.

4. The preparation method according to claim 1, characterized in that: The particle size of the Ta-10W spherical powder is 15-53 μm, and the sphericity is greater than 99%. The particle size of the spherical tantalum powder is 15-53 μm, and the sphericity is greater than 99%.

5. The preparation method according to claim 1, characterized in that: The parameters of the laser selective melting process are: laser power of 375 to 450 W, scanning speed of 550 to 750 mm / min, scanning spacing of 0.1 mm, and layer thickness of 0.03 mm.

6. The preparation method according to claim 1, characterized in that: The vacuum degree of stress relief heat treatment is less than 3×10 - 3 Pa, temperature is 1250℃ to 1400℃.

7. The preparation method according to claim 1, characterized in that: The chemical composition of the spherical tantalum powder meets the following conditions: Carbon content ≤7ppm, Hydrogen content ≤17ppm, Oxygen content ≤160ppm, Nitrogen content ≤20ppm, The purity of tantalum is greater than 99.995%.

8. The preparation method according to claim 1, characterized in that: The chemical composition of the Ta-10W spherical powder meets the following conditions: Carbon content ≤7ppm, Hydrogen content ≤15ppm, Oxygen content ≤100ppm, Nitrogen content ≤20ppm, Iron content ≤3ppm, The tungsten content is 9-11%, The contents of other impurities such as nickel, silicon, niobium and titanium meet the standard requirements.

9. A tantalum-tungsten alloy, characterized in that: Prepared according to the preparation method described in any one of claims 1-8.

10. The tantalum-tungsten alloy according to claim 9, characterized in that: The tantalum-tungsten alloy has a tensile strength Rm of 550 to 726 MPa, a yield strength Rp0.2 of 473 to 665 MPa, and an elongation A of 29% to 40%.

Citation Information

Patent Citations

  • Tantalum-tungsten alloy used for 3D printing and method for preparing tantalum-tungsten alloy thin-wall plate

    CN112795828A

  • Preparation process of tantalum-tungsten alloy based on laser selective melting and tantalum-tungsten alloy

    CN113319292B

  • Tantalum-tungsten alloy products and preparation methods thereof

    CN115106540B

Cited By

  • Tantalum-tungsten alloy spherical powder and preparation method and additive manufacturing method thereof

    CN121776474A

  • Tantalum-tungsten-based nano composite target material and preparation method thereof

    CN122012976A

  • A tantalum-tungsten based nanocomposite target and its preparation method

    CN122012976B